El regreso inesperado. Migración y nuevos arreglos residenciales - Patricia Arias (Les Cahiers ALHIM)
The aim of this paper is to show how changes in the marriages have resulted in residential retreats and economic arrangements. They have created - or recreated - power relationships, subordination and gender inequality for women in their households. But these power relationships, subordination and gender inequalities emanate not only from the relations between couples in marital homes. Trends, such as the non-formation or dissolution of unions have shifted relationships, imbalances, tensions, conflicts, traditional gender violence, from the relationship of the spouse and his family -as was traditional in Mexico- to the original domestic group of the women. That is where new imbalances and gender subordination have emerged, framing the lives of women today. The new phase of the Mexico-US migration has tended to exacerbate these demographic trends and domestic tensions within the original domestic group of the women.